A novel prognostic model for patients with colon adenocarcinoma - Yin, Chengliang; Wang, Wanling; Cao, Wenzhe; Chen, Yuanyuan; Sun, Xiaochun; He, Kunlun (Frontiers in Endocrinology, 2023)
Backgroud: Colon adenocarcinoma (COAD) is a highly heterogeneous disease, which makes the prognostic prediction challenging. The purpose of this study was to investigate the epidemiological characteristics, prognostic factors, and survival rates of COAD patients to establish and validate a predictive clinical model (nomogram) for COAD patients. Methods: COAD patients diagnosed between 1983 and 2015 were identified from the SEER database. Disease-specific survival (DSS) and overall survival (OS) was assessed applying the log-rank test and Kaplan-Meier approach. Univariate and Multivariate Cox regression analyses were used to discover independent prognostic factors for OS and DSS. Nomograms to predict survival possibilities were constructed based on the identified independent prognostic factors.The predictive ability of the nomogram model was assessed by calibration plots and receiver operating characteristics (ROCs) curve, while decision curve analysis (DCA) and clinical impact curve (CIC) were applied to measure predictive accuracy and clinical practice. Moreover, the nomogram was validated by the internal cohort. Results: A total of 104933 patients were identified with COAD, including 31479 females and 73454 males. Follow-up study ranges from 22 to 88 months, among which average is 46 months..Multivariate Cox regression analysis revealed that age, gender, race, site_recode_ICD, grade, CS_tumor_size and Transfer were independent prognostic factors for survival. Nomograms specifically for COAD were constructed to predict 1-, 3-, and 5-year DSS and OS possibility, respectively. The concordance index (C-index) and calibration plots showed the established nomograms had a robust prediction capability. The clinical decision chart (DCA) and clinical impact chart (CIC) were good for predictive accuracy and clinical practice. Conclusion: The incidence has been steadily increasing over the past four decades. Survival has improved in recent years. Surgery or chemotherapy could provide better DSS and OS. The established nomograms specifically for COAD were robust and accurate in predicting 1-, 3-, and 5-year DSS. Our study is of great significance for treatment and targeted follow-up. It also provides guidance for further prospective studies.